Are our patients different? A 5-year review of cervical cancer cases managed in tertiary Gynaecological Cancer Unit in Malaysia - Mat Ali, Norhuda; Zakaria, Alik Riasadesa; Awang, Mokhtar (2015)
Objective: The purpose of this review is examine the clinicopathological characteristics of cervical cancer treated in this situation from 2010 to 2014. Method: This is an observational retrospective study. All cases of cervical cancer treated in this institution from January 2010 until December 2014 were reviewed. Clinicopathological characteristics were recorded and analysed using SPSS version 20. Result:There were 31 cases of cervical carcinoma identified during that 5-year period. The mean age at diagnosis was 51.0 0±12.7 years(range,29-78 years).The majority of them (87%) were diagnosed before the age 70. None of the patients participated in cervical cancer screening programme and as a result less than 10% of women were diagnosed following an abnormal pap smear test. More than 90& were symptomatic, out of 82% were abnormal per vaginal bleeding and the remaining 11% and 7% were postcoital bleeding and compressive symptoms respectively. Risk factors for cervical cancer were identified in less than a third of the patients. Premorbid medical conditions were identified in only 50% of patinets and 94% were hypertension and/or diabetes mellitus. Similarly, the majority (94%) were categorised as having either ECOG functional class 0 and 1 i.e. 81 % and 13% respectively. There was an equal breakdown between squamous cell carcinoma(SCC) and adenocarcinoma(ACC), which was 48.4% each and the remaining 3.2% were others. For SCC,nearly all(94%)were large cell non-keratinising SCC with only 6% were large cell keratinising SCC subtype. As for ACC, the majority type were mucious endocervical subtype (47%), 40% were classified and the remainig 13% were others. Almost all (96.8%) patients had an examination under anaesthesia (EUA) and diagnostic imaging in the form of computer axial tomography(CT) scan to rule out the locoregional and distance metasis. Just above the half(55%) of the patient presented with stage 1b i.e. 29% 1b1 and another 26% 1b2. Stage 2 contributed to about 23% and which 13% were 2a and 10% were 2b. Stage 3 and stage 4 disease accounted for the remaining 9% and 13% respectively. About two-third of patients went on to have treatment with us and the remaining one- third sought an alternative form of treatment. Out of this, 47% had Wertheim’s hysterectomy,6% had neoadjuvant chemotherapy, followed by Wertheim’s hysterectomy, 20% had concurrent chemoradiation and the remaining 13% had palliative treatment. From the 16 patients who had Wertheim’s hysterectomy, 8 of them (50%) required further adjuvant treatment in the form of radiotherapy. Conclusion: The incidence of adinocarcinoma is higher than other study. Only one third of our patients had early disease at presentation, which is likely to poor cervical smear uptake. Our adjuvant radiotherapy rate was higher compared to others as most of our patients preferred surgery (even they needed adjuvant radiotherapy) compared to concurrent radiotherapy alone.